Fatigue damage accumulation in aluminum 7050-T7451 alloy subjected to block programs loading under step-down sequence - Carvalho, Andre L. M.; Martins, Juliana P.; Voorlwad, Herman J. C. [UNESP]; Lukas, P. (Elsevier B.V., 2010)
In this paper the fatigue damage accumulation under block program loading is investigated. Alternative flexion bending fatigue tests with a single change in stress amplitude are performed at room temperature for step-down sequence with two-step and three-step loading. The fatigue strength of aluminum 7050-T7451 alloy under block loading is investigated through comparison between the remaining cycles and consumed cycles ratios. The experimental results from the blocks loading fatigue tests are compared with the predictions using Miner's rule. It is shown that, two-step the fatigue strength is enhanced for smaller consumed fatigue loading and the cumulative fatigue damage calculated in accordance with the LDR, for three-step the fatigue strength occurs to a higher number of consume fatigue loading and the LDR rule trend to underestimate the fatigue life and the accumulative damage becomes higher than unity. (C) 2010 Published by Elsevier Ltd.
Keywords: Block program loading; Fatigue damage accumulation; fatigue loading and aluminum alloy